Studi Lokalitas: - Saeful Anam (Program Studi PGRA, 2017)
This paper explores about Aesthetic Culture Kercengan as Public Social Harmonization in Bawean Gresik. Culture as local wisdom has added value, not least Kercengan culture, for the people of Bawean Gresik, Kercengan is one of culture that is believed to give the harmonious, peaceful and full of beauty. It can be juxtaposed with the multiple cultures that spread in Java, like, Grebek Maulud, Grebek Suro, or Gendingan Java. The Cultures ought to be maintained and preserved. This study aims to know how to form the cultural aesthetics Kercengan as social harmonization in Bawean Gresik. Design of this research is descriptive qualitative with phenomenological approach, while the results showed that the kercengan which has three functions in society. First, as social control of society. Second, have the power to be used as a medium of propaganda, which is done with the feel of a typical Islamic. Third as the identity of harmony in diversity, that is, as a medium to uphold a sense of unity in life. The aesthetic value is situated on the beauty of cultural performances Kercengan done, as the analogy of diverse social life.